MANAJEMEN GURU BIMBINGAN KONSELING DI SMA NEGERI 1 BANDA ACEH - M. Ramzi; Murniati AR; Bahrun . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
Management of guidance and counseling teacher is an important factor in improving the quality of education. Management of guidance and counseling will be able to provide effective guidance service. This study was conducted to find out the overview of program, implementation, evaluation, and obtascles faced by guidance and counseling teachers in SMA ( senior high school) 1 Banda Aceh. The research method used was qualitative approach. The data collection was done by means of observation, interview, documentation, and data analysis. The subjects of the study were principals, guidance and counseling teachers, and student. 1). The programs of guidance and counseling teachers whic hare in forms of annual, monthly, and daily RPL programs were well arranged, 2). The implementasion of guidance service was done based on the curriculum and certain cases faced by the students, and the implementasion of the program consists of guidance service for students, 3). The evaluation done by guidance and counseling teachers was based on the cases that had been solved including violation in discipline such as coming late to school, using inappropriate school attributes, and carrying mobile phone to school. The evaluation conducted by taecher and counseling guidance was in accordance with the problems faced by the students. 4). One of the obstacles faced by guidance and counseling teachers is lack of support and collaborative work with homeroom teachers and 0SIS supervisor in resolving students’ problems. Moreover, there were only few books avaible related to guidance and counseling service in the school library.Keywords: management, guidance, and counseling teachers.